2022
DOI: 10.1055/s-0042-1742314
|View full text |Cite
|
Sign up to set email alerts
|

Main Complications during Pregnancy and Recommendations for Adequate Antenatal Care in Sickle Cell Disease: A Literature Review

Abstract: Sickle cell disease (SCD) is the most common monogenic disease worldwide, with a variable prevalence in each continent. A single nucleotide substitution leads to an amino-acid change in the β-globin chain, altering the normal structure ofhemoglobin, which is then called hemoglobin S inherited in homozygosity (HbSS) or double heterozygosity (HbSC, HbSβ), and leads to chronic hemolysis, vaso-occlusion, inflammation, and endothelium activation. Pregnant women with SCD are at a higher risk of developing maternal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Regarding more recently approved SCA therapies, there are no available data on antioxidant L‐glutamine use in pregnant women or animal studies to inform a drug‐associated risk of major birth defects and miscarriage 24 . However, as L‐glutamine is a common amino acid found in the body, it is generally considered to be safe 48 . For the oxygen‐affinity modulator voxelotor, no adverse developmental effects were found in animal reproduction studies, but experiments only tested at exposures up to 2.8‐times (rats) and 0.3‐times (rabbits) the maximum recommended human dose 26 .…”
Section: Antenatal Pharmacotherapy Options For Scamentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding more recently approved SCA therapies, there are no available data on antioxidant L‐glutamine use in pregnant women or animal studies to inform a drug‐associated risk of major birth defects and miscarriage 24 . However, as L‐glutamine is a common amino acid found in the body, it is generally considered to be safe 48 . For the oxygen‐affinity modulator voxelotor, no adverse developmental effects were found in animal reproduction studies, but experiments only tested at exposures up to 2.8‐times (rats) and 0.3‐times (rabbits) the maximum recommended human dose 26 .…”
Section: Antenatal Pharmacotherapy Options For Scamentioning
confidence: 99%
“…24 However, as L-glutamine is a common amino acid found in the body, it is generally considered to be safe. 48 For the oxygen-affinity modulator voxelotor, no adverse developmental effects were found in animal reproduction studies, but experiments only tested at exposures up to 2.8-times (rats) and 0.3-times (rabbits) the maximum recommended human dose. 26 So far no teratogenesis data are available for the anti-adhesive monoclonal antibody crizanlizumab, although IgG2 is recognized to be the least efficiently transported IgG subclass across the human placenta.…”
Section: Antenatal Pharmacother Apy Op Ti On S For Sc Amentioning
confidence: 99%
“…1 In the Jamaican pregnant population, 2.8% of women have SCD. 2 This group of disorders is highly associated with increased maternal morbidity/mortality, 3 with the most common cause of maternal death being acute chest syndrome (ACS). 2 …”
Section: Introductionmentioning
confidence: 99%
“…1 In the Jamaican pregnant population, 2.8% of women have SCD. 2 This group of disorders is highly associated with increased maternal morbidity/mortality, 3 with the most common cause of maternal death being acute chest syndrome (ACS). 2 COVID-19, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was officially declared a pandemic in March 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Of the other SCD variants, the most common is SC hemoglobinopathy (HbSC). Several studies have reported maternal and fetal complications in pregnant women with SCD: perinatal mortality, preterm labor, fetal growth restriction, preeclampsia, acute painful crises, and urinary and pulmonary infections [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%